Christmas Greetings from the Perspective of Inter-Religious Students and Academics in Medan - Harahap, Muhammad Yasril; Harahap, Aprilinda; Ritonga, Ridwan; Awang, Jaffary (Al-Jadwa: Jurnal Studi Islam, 2025)
The diversity of religions and cultures in Indonesia often causes social problems, one of which is related to religious issues, such as giving Christmas greetings, which often cause differences of opinion among the community. This study aims to analyze how students and academics in Medan view Christmas greetings and to understand the influence of religion and social interaction on their attitudes. The method used is a descriptive qualitative approach with field research. We obtained primary data through in-depth interviews with key informants, including Muslim and Christian students and academics, using semi-structured interview techniques. We obtained secondary data from relevant literature studies. We carried out thematic data analysis to identify the main themes related to Christmas greetings. The results of the study show variations in views influenced by religion, personal understanding, and social interaction. Muslim students and academics are generally careful in giving Christmas greetings, while Christian students and academics are more open and see it as part of a social tradition. This study contributes to the understanding of interfaith dynamics in Indonesia and underlines the importance of dialogue and tolerance in a multicultural society.